Validity of Interactive Learning Media Based on Moodle's Learning Management System with Three Chemical Representative Levels (Macroscopic, Submicroscopic, and Symbolic) in Electrolysis Cell Sub Material - Kholifatur Rosyidah; Sukarmin Sukarmin (Universitas Lampung, 2021)
Validity of Interactive Learning Media Based on Moodle’s Learning Management System with Three Chemical Representative Levels (Macroscopic, Submicroscopic, and Symbolic) in Electrolysis Cell Sub Material. This study aims to determine the validity of Interactive Learning Media Based on the Moodle Learning Management System with Three Chemical Representative Levels (Macroscopic, Submicroscopic, and Symbolic) in the Electrolysis Cell Sub Material seen from the content and construct validity. This study uses a Research and Development (RD) type of research which only reached the design revision step from the validation results. This study used an interactive media review sheet instrument and an interactive media validation sheet. Based on the validation results, it shows that the developed interactive media obtained a percentage of 92,5% for content validity which was included in the very valid category, and 88% for construct validity which was in the very valid category to use as a media to prevent misconceptions in students with three levels of chemical representation. Keywords: Interactive media, Moodle, three levels of Chemical Representation, Electrolysis Cell.DOI:10.23960/jppk.v10.i3.2021.15